2021
DOI: 10.1007/s11665-021-05619-1
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural, Mechanical, and Fracture Characterization of Metal Matrix Composite Manufactured by Accumulative Roll Bonding

Abstract: Accumulative roll bonding is a severe plastic forming process recently proposed to manufacture ceramic particle reinforced-multi-layered metal matrix composites. In this work, low-cost composite multi-layered laminate was produced by roll bonding commercially pure aluminium 1100 with 5% in volume of reinforcing micro-scale silicon carbide particles. Microstructural features, hardness, tensile properties in the presence of stress concentrators, and wear resistance were assessed.Fracture surface inspection was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Göken and Höppel [ 30 ] were produced uniform distribution of particles composite and found that the reinforcement of particles results in the improvements of mechanical properties. Pereira et al [ 31 ] found that the finer ceramic particles can enhance the composite strength, particularly through ARB cycles. Khoramkhorshid et al [ 32 ] confirmed that ceramic particles with Al matrix through ARB show good bonding strength and excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Göken and Höppel [ 30 ] were produced uniform distribution of particles composite and found that the reinforcement of particles results in the improvements of mechanical properties. Pereira et al [ 31 ] found that the finer ceramic particles can enhance the composite strength, particularly through ARB cycles. Khoramkhorshid et al [ 32 ] confirmed that ceramic particles with Al matrix through ARB show good bonding strength and excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For lamellar materials, especially those that are produced by such processes as cold roll bonding (CRB) or accumulative roll bonding (ARB), great attempts have been made to relate production processes to the mechanical properties [1][2][3][4][5][6][7][8][9][10][11]. In the case of the ARB process, most researchers have claimed that the nucleation and propagation of micro-voids during ARB cycles to underlie the failure of metallic composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (2021) conducted experimental and finite element method (FEM) study of cutting mechanism and damage behavior of ceramic particles in orthogonal cutting SiCp/Al composites. Pereira et al (2021) conducted microstructural, mechanical, and facture characterization of metal matrix composite manufactured by accumulative roll bonding. Gao et al (2019) studied strengthening and fracture behaviors in SiCp/Al composites with network particle distribution architecture.…”
mentioning
confidence: 99%